The system efficiency improvement, equitization and renewables project = (The World Bank in Vietnam (WB), 2003)
The objective of the Project is to improve the overall efficiency of power system services, particularly to the poor in rural areas, by optimizing the transmission systems, and upgrading sub-transmissions, and medium voltage distribution lines for rural electrification. The project components are as follows: 1) Power system efficiency will be improved by upgrading the 500 KV, and 200 KV transmission networks, and associated substations, which includes the installation of capacitors to selected substations. The system peak load will be reduced, through the implementation of several demand-side management (DSM) measures - to be supported by an associated DSM and Energy Efficiency Project, financed by the Global Environment Facility and the private sector - in an aim to further DSM impacts, and catalyze the development of sustainable energy efficiency. 2) Rural electricity access will be improved by upgrading, and strengthening the 110 KV sub-transmission line, and substations, restoring five existing hydropower plants, and, by construction of a small-scale hybrid wind-diesel power plant at Phu Quoc Island. Moreover, a pilot of twenty community-based hybrid renewable-energy grids in remote areas, will be tried and developed. 3) Sector reform, and institutional development will be pursued, through improvements in the management information system, the creation of one District, and several commune-level joint-stock distribution companies, and, by strengthening the regulation, planning, and implementation capacity for renewable electricity. To this end, operational training, and technical assistance will be provided.